1996
DOI: 10.1271/bbb.60.1017
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Interleukin-2 Receptor Expression on Mouse CD4+T Cells by Bovine κ-Caseinoglycopeptide

Abstract: 8m-ine K-caseinoglycopeptide (residues lOfr169, CGP) completely inhibited the PH A-induced proliferation of mouse splenocytes when CGP was added simultaneously with PHA. The inhibitory effect, however, was reduced to about one-half when CGP was added after 24 h of cultinting the splenocytes with PHA or when anti-IL-Ira antibody was added simultaneously with PHA and CGP. On the other hand, CG P bound to mouse CD4 + T cells but not to CDS + T cells. CGP suppressed IL-2 receptor expression of the PHA-stimulated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 1 publication
2
24
0
Order By: Relevance
“…CMP also exerts immunomodulating activities, as it inhibits mitogens from inducing the proliferation of lymphocytes, and can even induce apoptosis of certain lymphocytes (Matin & Otani, 2000;Monnai & Otani, 1997;Otani, Horimoto, & Monnai, 1996;Otani, Monnai, Kawasaki, Kawakami, & Tanimoto, 1995). These immunomodulatory effects depend both on the polypeptide portion of CMP and on the presence of sialic acid (Li & Mine, 2004a;, but also on the immunological responsiveness of the mouse strain used for the cell proliferation assay (Otani, Horimoto, Matin, Ohnuki, & Kawahara, 2005).…”
Section: Health Effects Of Intact Cmpmentioning
confidence: 99%
“…CMP also exerts immunomodulating activities, as it inhibits mitogens from inducing the proliferation of lymphocytes, and can even induce apoptosis of certain lymphocytes (Matin & Otani, 2000;Monnai & Otani, 1997;Otani, Horimoto, & Monnai, 1996;Otani, Monnai, Kawasaki, Kawakami, & Tanimoto, 1995). These immunomodulatory effects depend both on the polypeptide portion of CMP and on the presence of sialic acid (Li & Mine, 2004a;, but also on the immunological responsiveness of the mouse strain used for the cell proliferation assay (Otani, Horimoto, Matin, Ohnuki, & Kawahara, 2005).…”
Section: Health Effects Of Intact Cmpmentioning
confidence: 99%
“…This peptide inhibits lipopolysaccharide and phytohemagglutinin-induced proliferation of mouse splenocytes and rabbit Peyer's patch cells [15], upregulates the expression of IL-1 receptor antagonist-like component in mouse lymphocytes [16] and suppresses the expression of IL-2 receptor on mouse CD4+ T cells [17]. It enhances the proliferation and the phagocytic activities of the human macrophage cell line U937 [18] and upregulates the secretion of tumor necrosis factor (TNF)-α, IL-1β, and IL-18 in human monocyte THP-1 cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore milk and colostrum have many bioactivity. Recently, it has been reported that kappa-casein and its digests in milk, which has been considered as just a protein nutrient, possess bioactive activity [7][8][9][10]. Furthermore, colostrum also contains living lymphocytes and mammary epithelial cells that express the mRNA of cytokines [11][12][13].…”
Section: Introductionmentioning
confidence: 99%